2021
DOI: 10.3389/fcell.2021.678209
|View full text |Cite
|
Sign up to set email alerts
|

Ivacaftor Inhibits Glioblastoma Stem Cell Maintenance and Tumor Progression

Abstract: Glioblastoma (GBM) is the most common and malignant primary brain tumor. Glioblastoma stem cells (GSCs) not only initiate and sustain uncontrolled cell proliferation but also resistant to conventional clinical therapies including temozolomide (TMZ) dependent chemotherapy and radiotherapy, implying that there is an urgent need to identify new therapeutic strategies especially specific targeting GSCs. Here, we provide evidence showing that ivacaftor commonly applied in cystic fibrosis therapy acts as a potent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Recently, several innovative pre-clinical studies have emerged to enhance tumor inhibiting efficacy of TMZ [ 4 , 7 , 33 ]. Different treatment strategies based on various mechanisms of TMZ resistance can reduce GBM resistance to TMZ to some extent both in vitro and in vivo, and may offer new hope to improve GBM patients prognosis [ 8 , 11 , 12 , 34 ]. More studies have well demonstrated that GSCs were more resistant to TMZ than their differentiated progeny cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several innovative pre-clinical studies have emerged to enhance tumor inhibiting efficacy of TMZ [ 4 , 7 , 33 ]. Different treatment strategies based on various mechanisms of TMZ resistance can reduce GBM resistance to TMZ to some extent both in vitro and in vivo, and may offer new hope to improve GBM patients prognosis [ 8 , 11 , 12 , 34 ]. More studies have well demonstrated that GSCs were more resistant to TMZ than their differentiated progeny cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2,[4][5][6][7][8]. Several studies have suggested that GBMderived glioma stem cells (GSCs) may play vital roles on formation of GBM resistance to TMZ [9][10][11]. GSCs had the features of selfrenewal, infinite proliferation, multi-potential differentiation, strong infiltration, and migration abilities [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Many inhibitors have been reported to induce cancer regression in a different type of cancer, yet only a small portion of them have been applied in clinical trials ( 149 151 ). Recently, the characterization and application of antisense oligonucleotide (ASO) opens a new avenue for the development of cancer therapeutics, and many of them have been implemented in different clinical trials ( 152 154 ).…”
Section: Clinical Relevance Of Lncrna In Tcmentioning
confidence: 99%
“…Glioblastoma (GBM) is a primary brain tumor of the central nervous system in adults. It has been well-recognized that GBM was initiated by a subpopulation of cells termed glioblastoma stem cells (GSCs) 1 , 2 . Central nervous system (CNS) gliomas are classified into 4 grades according to the WHO classification.…”
Section: Introductionmentioning
confidence: 99%
“…The median survival of patients with GBM is only 14.6 months. Currently, conventional treatment includes neurosurgery, temozolomide (TMZ) dependent chemotherapy 1 , 2 , and chemotherapy. Although GBM cells rarely metastasize to other body organs, the treatment of GBM remains ineffective.…”
Section: Introductionmentioning
confidence: 99%